Factors associated with inpatient complications among patients with obesity and COVID‐19 at an urban safety‐net hospital: A retrospective cohort study. (15th August 2022) - Ryan, Tyler J.; Heyman, Annie S.; Mulvey, Elizabeth N.; McLaughlin, Angela; Rizo, Ivania M.; Assoumou, Sabrina A.
Abstract: Objective: Obesity increases morbidity and mortality from Coronavirus disease 2019 (COVID‐19). This study characterized inpatient complications among patients with obesity and COVID‐19—including myocardial infarction, renal failure requiring dialysis, stroke, secondary bacterial infection, and venous thromboembolism—and identified factors associated with developing at least one inpatient complication at a safety‐net hospital with a diverse cohort. Methods: A retrospective review was performed of all patients admitted for ≥3 days with COVID‐19 between 16 March 2020, and 8 April 2020. Logistic regression identified factors associated with developing at least one COVID‐19‐related complication among patients with obesity (body mass index ≥30 kg/m 2 ). Results: 374 patients were included; 53.7% were classified as having obesity, 43.9% identified as Black, and 38.5% identified as Latino or Hispanic. Obesity was not associated with having at least one inpatient complication on multivariable analysis, but increased age (aOR 1.02, [95% CI 1.01–1.04], p  = 0.010) and obstructive sleep apnea (aOR 2.25, [1.08–4.85], p  = 0.034) were associated with this outcome. Conclusions: Obesity was not associated with specified inpatient complications among patients with COVID‐19 admitted to a health system caring for diverse patients. Future studies should incorporate larger cohorts and reflect newer treatment protocols.